Stability Analysis of Single-Phase Low-Voltage AC Microgrids with Constant Power Terminals (2019)
This express brief presents the stability analysis of single-phase microgrids (SP-MG) operating under master-slave connection with constant power terminals. The SP-MG is composed of linear elements, nonlinear loads, and distributed generators modeled as PQ constant terminals interconnected through power electronic converters. Lyapunov's direct method through a Hamiltonian representation of the grid is used to demonstrate stability. The non-autonomous model of the SP-MG is transformed into an autonomous equivalent model based on the dynamics of the error. The proposed analysis shows that if there is an admissible trajectory {x} ^{\boldsymbol {\star }} solution of the power flow equations, then the SP-MG is stable in the sense of Lyapunov. © 2004-2012 IEEE.